The Implementation of Media Culture Through Social Media to Bring Up Students` Social Capital in Social Studies Education - Fadlurrahman, F (International Journal Pedagogy of Social Studies, 2021)
The purpose of this study is to describe how the efforts of social studies teachers in implementing social-based learning, both the social capital of students through uploads of social studies learning on social media and to describe the existing social capital through the interests and talents of the extra-curricular students/communities that follow. The findings show that the efforts made by the school through the learning teacher, especially social studies, in the implementation of BDR include several stages of material and learning methods with each MGMP, the implementation stage carried out by teachers both at school and at home and the evaluation stage which is carried out every day after learning hours of teaching and learning is complete. Trust is built by the school through the class guardian to always remind and enter students during this BDR activity. Overall, the results of this study indicate that learning using cultural media through social media is an alternative to learning by promoting communication in various directions, but it has not been able to make learning fun in various schools for reasons of facilities and infrastructure and the readiness of students and guardians of students.